ANALISIS ASUHAN KEPERAWATAN KELUARGA DENGAN INTERVENSI FOOD DIARY TERHADAP PENURUNAN BERAT BADAN PADA REMAJA DI RW 06 KELURAHAN GROGOL LIMO DEPOK - Ni Made Anggun Millenia (2023)
Obesity is the accumulation of excessive fat that can lead to health risks. In adolescence, obesity is at high risk and the incidence of obesity in adolescents is an indicator of a health problem and an increased risk of non-communicable diseases that occur in society. Food diary is a written record containing the type and amount of food and drinks consumed by a person during a certain period of time which aims to increase adolescents' awareness of healthy diet and lifestyle, and increase confidence in controlling weight. The purpose of this paper is to analyze nursing care with food diary interventions for weight loss in adolescents, where interventions are carried out by adolescents for 30 days by recording the types of food, drinks, and snacks consumed every day and monitoring weight every week. The results showed a significant effect on weight loss in obese adolescents by providing interventions in the form of a food diary, where there was a decrease in body weight in managed and resume patients by 1.4 kg and 1.1 kg. It is recommended that the use of tools or media to provide information about obesity and dietary regulation, especially in adolescents, can be further developed and can be the basis for interventions for providing nursing care, especially for obese adolescents for health service providers.